Human - Wildlife Conflicts in Europe Fisheries and Fish-eating Vertebrates as a Model Case - Klenke, Reinhard A.; Ring, Irene; Kranz, Andreas; Jepsen, Niels; Rauschmayer, Felix; Henle, Klaus (Environmental Science,, 2013)
This book is about conflicts between different stakeholder groups triggered by protected species that compete with humans for natural resources. It presents key ecological features of typical conflict species and mitigation strategies including technical mitigation, policy instruments and the design of participatory decision strategies involving relevant stakeholders. The book provides not only case studies from various European countries, it also presents a framework for the development of biodiversity conflict reconciliation action plans that can be used globally.